AFIKSASI BAHASA JAWA KRAMA INGGIL DIALEK JAWA TIMUR DI DESA SUAK TEMENGGUNG KECAMATAN PEKAITAN KABUPATEN ROKAN HILIR - Andriana, Siti; Sinaga, Mangatur; Faizah, Hasnah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstraks: This study aimed to describe the affixation cinsisting of a prefiks, infiks, suffix, confix and affix combinations (combined) in the Java language Krama Inggil East Javanese dialect in the village Suak Temenggung Pekaitan District of Rokan Hilir. This study uses a qualitative method. The data source of this rescarch is the Java language speakers Krama Inggil East Javanese dialect in the village Suak Temenggung Pekaitan District of Rokan Hilir. This research data is affixed word. Collecting data using the techniques of interviewing, recording, see note and documentation while the data analysis techniques that is descriptive. The study concluded that the affixation of Java language speakers Krama Inggil East Javanese dialect in the village Suak Temenggung Pekaitan District of Rokan Hilir consist of a prefix, infix, suffix, confik and the combined category has the uniqueness of each affix are able to adhere to the basic word except in combination affixes (The combined).Keyword: affixation, the Java language Krama Inggil, East Java dialect.